ANALISIS EPISTEMOLOGIS TERHADAP KRITERIA MUFASSIR: TELAAH ATAS SUMBER, METODE DAN VALIDITAS ILMU DALAM PERSPEKTIF USHUL AL-TAFSIR - Siti Nurhidayati; Annisa; Melani Rosada; Marni Lubis; Anwar Sidik (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Qur'anic interpretation is a complex scholarly activity that demands intellectual, methodological, and spiritual competencies from a mufassir (interpreter). The study of Ushul al-Tafsir (principles of Qur'anic exegesis) is essential for understanding the epistemological foundations underpinning the criteria of a mufassir, including sources of knowledge, interpretative methods, and the validity of the sciences involved. This research aims to conduct an epistemological analysis of the criteria for mufassirs by examining the dimensions of sources, methods, and the legitimacy of knowledge within the perspective of Ushul al-Tafsir. A qualitative approach based on literature review was employed, focusing on classical works such as al-Burhān and al-Itqān, alongside contemporary thoughts from scholars like Muhammad Abduh, Fazlur Rahman, and Muhammad Arkoun. The findings reveal a significant epistemological shift from a textual-traditional model to a more rational and contextual approach, where the validity of interpretation is no longer solely dependent on authoritative transmission but also on methodological integrity and socio-cultural relevance. These results underscore the necessity of reformulating the criteria of a mufassir to integrate traditional authority with modern scientific approaches. Consequently, there is a need to strengthen Qur'anic interpretation curricula based on a dynamic Islamic epistemology to preserve the authenticity and sustainability of tafsir studies in contemporary contexts.